Presidential succession and its constitutional dilemna averting a crisis in democratic legitimacy (Philippine Law Journal, 2021)
Under the Constitution, only the vice president can fully succeed the presidency upon the death of the president. While there is a "succession" scheme in the event that the Offices of the President and the Vice-President become simultaneously vacant, the officials who are next in the line of succession—the senate president, or in his or her absence, the house speaker—will only serve as "acting president" until a special election is conducted within a specific timeframe. But what happens when the senate president and the house speaker perish together with the president and the vice- president? Two bills were filed in the 18th Congress in an attempt to address this question. These bills expressly sought to adopt the American practice of having a "designated survivor" who would be sequestered to a secure location during major govemment events. However, it is argued that reference to U.S. succession laws is misplaced since the Philippine law on presidential succession has long diverged from its American counterpart. Furthermore, these bills would only address one of the two scenarios that may lead to a constitutional crisis, in the event of simultaneous vacancies in the top four elective offices of the Philippine government. The other scenario, which is argued as a fatal flaw in drafting the Constitution, may only be remedied through a constitutional amendment.